Perencanaan Kawasan Wisata Sungai Saddang di Kabupaten Enrekang - Haidir Hatta; Pratiwi Juniar A. Gani; Andi Muhammad Ikhsan (Universitas Medan Area, 2026)
Natural and cultural resources that have the potential to be developed. Saddang River, also known as SWISS (Around Saddang River Area), offers beautiful panoramas, cool water, and wide shores which are an attraction for domestic and foreign tourists. Tourism visit data shows a fluctuating trend in the 2018–2023 period. influenced by external and internal factors. The research method includes collecting primary data through observation and interviews, as well as secondary data through literature studies and regional map analysis. The study results emphasize the importance of planning facilities and infrastructure that meet standards to support tourism development, including the provision of regional culinary facilities. This planning is expected to increase tourist attractions, strengthen local cultural identity, and encourage regional economic growth.